1983
DOI: 10.1073/pnas.80.5.1232
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide chain initiation in eukaryotes: reversibility of the ternary complex-forming reaction.

Abstract: In the last step of polypeptide chain initiation in eukaryotes, the interaction of the 40S preinitiation complex eIF-2 GTP Met-tRNAj 4OS [the complex between the 40S ribosomal subunit and the ternary complex containing equimolar amounts of eukaryotic initiation factor 2 (eIF-2), GTP, and eukaryotic initiator methionyl tRNA (Met-tRNA;)] with a 60S ribosomal subunit in the presence of mRNA, cap binding protein (with "capped" messengers), ATP, and the initiation factors eIF-3, eIF-4a, -4b, -4c, and eIF-5, results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 13 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…It is remarkable that the phosphorylation sites in the smallest subunits of Drosophila and rabbit reticulocyte [37] eIF-2 are localized in a terminal fragment which suggests they are closely related. On the other hand, we have shown that, again as in the case of rabbit reticulocytes eIF-2 [38], the Drosophila factor can be isolated as an eIF-2 . GDP complex which is compatible with the notion that the factor has a high affinity for GDP.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is remarkable that the phosphorylation sites in the smallest subunits of Drosophila and rabbit reticulocyte [37] eIF-2 are localized in a terminal fragment which suggests they are closely related. On the other hand, we have shown that, again as in the case of rabbit reticulocytes eIF-2 [38], the Drosophila factor can be isolated as an eIF-2 . GDP complex which is compatible with the notion that the factor has a high affinity for GDP.…”
Section: Discussionmentioning
confidence: 97%
“…Samples contained in a final volume of 25 pl, 20 mM Hepes buffer pH 7.6, 100 mM KCl, 10 pM Mg(CH3C00)2, 1 mM dithiothreitol, 25 pg bovine serum albumin, 1.8 pM [3H]GDP (8900 cpm/pmol, Amersham) and eIF-2 (which, like reticulocyte eIF-2 [38], contains bound GDP) in the amounts indicated in each experiment. After incubation for 6 min at 25"C, samples were processed as described for ternary complex assay.…”
Section: Binary Complex Assaymentioning
confidence: 99%
“…In light of this result, the modest inhibition of eIF2␣ cleavage observed upon eIF2␣ phosphorylation in Fig. 7A is most likely due to the fact that GDP remains bound to a small fraction of purified eIF2 (26). As such, the Mg 2ϩ added to the kinase reaction would stabilize the binding of this GDP to eIF2 and inhibit its cleavage by caspases.…”
Section: Figmentioning
confidence: 97%
“…In the same figure the inhibitory effect of the reticulocyte heme-controlled eIF-2cu kinase is shown for comparison. This kinase phosphorylates the cy-or smallest subunit of peptide initiation factor 2, eIF&, and thereby inhibits binding of MettRNAf to 40 S ribosomal subunits [15] apparently by preventing the exchange of GTP for GDP from the GDP -eIF-2 complex [16]. On the basis of the weight of protein added to the lysate reaction mixture &spectrin is about half as inhibitory as the kinase, as judged from the initial slope of the inhibition curves.…”
Section: Resultsmentioning
confidence: 99%